Analisis Efek Material Bodi Terhadap Pengujian Impak Pada Motor Listrik Roda 3 E-Niaga Geni Biru - Nurzamzam, Wardian Andrie (Journal of New Energies and Manufacturing, 2023)
The body is a very important part of the vehicle, in addition to protecting other parts of a vehicle, it can also protect the driver. The choice of body material must be taken into account, therefore the selection of composite material as a material for the manufacture of the body has many advantages such as corrosion resistance, a very large hardness, and a very small density. This research was conducted to find out the impact toughness and fracture shape of the polymer matrix composite material using different volume variance fractions. The matrix used in Unsaturated Polyester Resin (UPRs). SHCP 2668 WNC uses a Methyl Ethyl Ketone Peroxide (MEKPO) catalyst and as a reinforcement using fiberglass CSM 300 with volume fraction variance 10%, 13%, 16%. The specimens were made using the ISO 179 standard with dimensions of 80 mm × 4mm × 10 mm and has a Notch standard of 45° with a depth of 2 mm. Making specimens using the Hand Lay Up using a mold. Furthermore, the impact test of the Charpy and photos of the microstructure was carried out on the fractures of each specimen variation. The results of the analysis of composite materials with glass fiber content concluded that in the impact test using the ISO 179 standard, the maximum impact strength occurred at 16% fiber volume with an average impact strength of 48.96 kJ/mm2, and the minimum impact strength occurred at a fiber volume of 10 % with an average impact strength of 17.81 kJ/mm2.